STUDI DESKRIPTIF KADAR DEBUPADA UNIT RAW MILL DI PT. HOLCIM INDONESIA Tbk CILACAP PLANT TAHUN 2016 - Herlianti, Afrilia; Subagiyo, Agus (Poltekkes Kemenkes Semarang, 2018)
AbstractDust Levels On Descriptive Study Unit At Raw Mill In Pt. Holcim Indonesia TbkCilacap Plant Year 2016A healthy environment is essential for businesses in the healthy sector. The growth of theindustrial sector is rapidly increasing impact on air pollution that can effect the health of the surrounding communities. PT. Holcim Indonesia TbkCilacap Plant is the third largest cement plant in Indonesia. Unit Raw Mill is one of the units in the cement manufacturing process that could potentially cause contamination in the workplace air of dust generated from the cement production process. The purpose of this research is to determine the amount of dust in the Raw Mill unit at PT. Holcim Indonesia TbkCilacap Plant in 2016.This research method is analyzed descriptively using crossectional approach to get an idea of the amount of dust in the unit Raw Mill in cement factory PT. Holcim Indonesia TbkCilacap Plant at the time of measurement. Research results obtained by measuring the amount of dust using a measuring device Environmental Particulate Air Monitoring 5000, type of measurement is a measurement of dust total duration 15 minutes/seconds. Measurements were taken at 5 poins showed the amount of dust in the unit Raw Mill in PT. Holcim Indonesia TbkCilacap Plant, earned an everage of 1,75 mg/m3 after convertion from 15 minutes to 8 hours namely 56 mg/m3 thus exceeding the NAB . With the highest level of dust 266,368 mg/m3 and the lowest 1,728 mg/m3. Standard used is Kepmenkes RI No 1405/MENKES/SK/XI/2002 about Terms of Work Environment Health, Office, and Industrial.Based on these results we can conclude the highest dust level 266,368 mg/m3 (exceeding NAB) and the lowest was 1,728 (not exceeding NAB). The advice given on the results of this study the PT. Holcim Indonesia TbkCilacap Plant provide cover on the engine flow of raw materials to reduce the spread of dust content with fiber for the production process still obseved.